Fezzan's economic conditions during the time of the French military administration 1943-1951 (Journal of Human Sciences, 2022)
This study deals with the economic conditions of the Fezzan region during the period of the French military administration 1943-1951 AD. the study also deals with the economic situation of the region when it was occupied by the Free France forces, and what are the economic procedures followed by the French military administration in the region throughout the period of its stay in the region until the end of December 1951 AD. We have to point out here that France did not leave the region after independence in late 1951 AD, but left in 1956 AD when signed the friendship and good-neighbourliness agreement with the government of Mustafa bin Halim.By economic conditions here we mean the financial, agricultural, and commercial aspect, as well as how taxes were collected within the region, and what they represent from the region's revenues.